Entrenamiento intervalado de alta intensidad en rugbistas juveniles de argentina - Cano, L. A.; Piza, Á. G.; Farfán, F. D. (Revista Internacional de Medicina y Ciencias de la Actividad Física y del Deporte, 2020)
The aim of the present study was to evaluate the influence of a High Intensity Interval Training protocol with straight running on the aerobic performance on male rugby players between 15 and 16 years old. Thirty three subjects voluntarily participated in the proposed training. Anthropometric measurements and estimates of maximal oxygen uptake (VO2max) were taken to characterize the subjects in the initial physical state. Subsequently, the maximal aerobic speed was estimated to set the training distances for each subject. The protocol was organized in six sessions divided in three weeks, consisting of two rounds of twelve repetitions with work intervals of ten seconds and ten seconds of passive pause. After six sessions estimates of VO2max were taken again. In the statistical treatment, non-parametric tests were used. The experimental group achieved a significant increase in VO2max of 12% (p <0.01), while the control group increased its yield by 6.8% (p <0.05).